Why and How Sexual Freedom Changed Western Criminal Law (19th and 20th centuries) - Aniceto Masferrer (Clio@Themis)
This article explains “why” and “how” the new paradigm of sexual freedom radically changed Western criminal law. “Why” touches upon the change in the moral sexual paradigm in the West at the cultural level. “How” describes the ways in which sexual (criminal) laws were reformed in accordance with the new cultural paradigm, describing the mutual influences between the US and Europe: while the US Supreme Court took the lead in forbidding states to make laws that might interfere in the sexual behaviour by resorting to the right to privacy – and this legal doctrine notably influenced most of European jurisdictions –, in Europe legal scholars and legislatures were the protagonists in undertaking criminal law reform, adjusting sexual criminal law to the new cultural ideas.